Analisis Risiko Overhaul SPM RU VI Balongan pada Galangan Surabaya menggunakan Metode FMEA dan FTA - risna prabandari; Irma Rustini Aju; Devina Puspita Sari (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
Single Point Mooring (SPM) is a system used to connect tankers with offshore installations to move oil or gas from ships to land. Therefore, SPM must be able to operate in good condition by carrying out routine maintenance. Surabaya Shipyard often receives requests for SPM repairs, but the risk level is often at a dangerous risk. This study aims to determine the right mitigation in overcoming the risk of SPM overhaul using the Failure Mode and Effect Analysis (FMEA) method to get the highest risk (RPN) and the Fault Tree Analysis (FTA) method which is useful for determining the factors that cause damage to the system. Based on the results of the study, 5 top events were obtained which were the priority risks in the overhaul process. From the 5 top events, 14 basic events were obtained which were the root cause of the failure of the SPM overhaul and mitigation must be carried out immediately so that the risk can be overcome and does not cause losses to Surabaya Shipyard.